บทบาทการส่งเสริมกิจการพระพุทธศาสนาตามหลักฆราวาสธรรม 4 ของสำนักงานพระพุทธศาสนา จังหวัดร้อยเอ็ด - นามปัญญา, เกษสุดา; โพธิ์ชัยหล้า, พรพิมล (วารสารรัฐศาสตร์สาส์น มหาวิทยาลัยมหามกุฏราชวิทยาลัย(Online); Vol 2 No 2 (2566): July-December 2023, 2023)
บทความวิจัยนี้มีวัตถุประสงค์ 1) เพื่อศึกษาระดับการส่งเสริมกิจการพระพุทธศาสนาตามหลักฆราวาสธรรม 4 ของสำนักงานพระพุทธศาสนา จังหวัดร้อยเอ็ด 2) เพื่อศึกษาเปรียบเทียบบทบาทการส่งเสริมกิจการพระพุทธศาสนาตามหลักฆราวาสธรรม 4 ของสำนักงานพระพุทธศาสนา จังหวัดร้อยเอ็ด จำแนกตาม อายุ พรรษา และระดับการศึกษา 3) เพื่อศึกษาข้อเสนอแนะแนวการพัฒนาบทบาทเพื่อส่งเสริมกิจการพระพุทธศาสนาตามหลักฆราวาสธรรม 4 ของสำนักงานพระพุทธศาสนาจังหวัดร้อยเอ็ด เป็นวิจัยเชิงปริมาณ กลุ่มตัวอย่างที่ใช้ในการวิจัย ได้แก่ คณะสงฆ์ในเขตการปกครองของจังหวัดร้อยเอ็ด จำนวน 364 รูป เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูลเป็นแบบสอบถามมาตราส่วนประมาณค่า 5 ระดับ สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และการวิเคราะห์ความแปรปรวนแบบทางเดียว (F-test) ผลการวิจัยพบว่า 1. บทบาทการส่งเสริมกิจการพระพุทธศาสนาตามหลักฆราวาสธรรม 4 ของสำนักงานพระพุทธศาสนา จังหวัดร้อยเอ็ด โดยรวมและรายด้านอยู่ในระดับมาก เมื่อพิจารณารายด้านโดยเรียงจากด้านที่มีค่าเฉลี่ยสูงไปต่ำ ได้แก่ ด้านการศึกษาสงเคราะห์ (ทมะ) รองลงมา ด้านการปกครอง (ขันติ) และด้านที่มีค่าเฉลี่ยต่ำที่สุด คือ ด้านการศาสนศึกษา (ทมะ) 2. ผลการเปรียบเทียบระดับความคิดเห็นที่มีต่อระดับบทบาทการส่งเสริมกิจการพระพุทธศาสนาตามหลักฆราวาสธรรม 4 ของสำนักงานพระพุทธศาสนา จังหวัดร้อยเอ็ด จำแนกตามอายุ พรรษา ระดับการศึกษา โดยรวม ด้านการปกครอง (ขันติ) และด้านการศึกษาสงเคราะห์ (ทมะ) คณะสงฆ์ที่มีระดับการศึกษาต่ำกว่าปริญญาตรีกับระดับปริญญาตรีและปริญญาโทมีความคิดเห็นที่แตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 นอกนั้นไม่แตกต่างกัน 3. ข้อเสนอแนะเกี่ยวกับบทบาทการส่งเสริมกิจการพระพุทธศาสนาตามหลักฆราวาสธรรม 4 ของสำนักงานพระพุทธศาสนา จังหวัดร้อยเอ็ด ควรมีการตรวจสอบประเมินผลการปฏิบัติงานอย่างสม่ำเสมอ เพื่อให้ทราบเกี่ยวกับปัญหา หรือจุดบกพร่อง เพื่อที่ในครั้งต่อไปจะได้ปรับปรุง พัฒนามากขึ้น ควรสนับสนุนรูปแบบการสอนและเผยแผ่หลักธรรมคำสอนด้วยวิธีการที่ทันสมัยโดยผ่านสื่อออนไลน์ ควรจัดให้มีกิจกรรมการส่งเสริมการศาสนศึกษา ทั้งแผนกบาลีแผนกธรรมและปริยัติสามัญ ตลอดการช่วยเหลือเกื้อกูลสถาบันการศึกษาต่างๆ ให้มากขึ้น ประสานงานกับหน่วยงานที่เกี่ยวข้อง ช่วยเหลือผู้ยากไร้และประสบภัย ควรมีการจัดกิจกรรมรักษาความสะอาดภายในวัด จัดการงบประมาณไปสนับสนุนจัดตั้งกองทุนสงเคราะห์การศึกษา ระดับ ประถมศึกษา มัธยมศึกษา และอุดมศึกษา เพื่อเป็นประโยชน์แก่ นักเรียนที่เป็นคนดี และเรียนดี แต่ด้อยโอกาสในการศึกษา The objectives of this research article were 1) to study the level of promoting  Buddhist Affairs based  on 4 Virtues for  a Good Household Life  of Roi Et office of Buddhism  2)  to study and compare the roles for promoting Buddhist Affairs based on 4 Virtues  for a Good Household Life of Roi Et office of Buddhism, classified by age, years of ordination, education level 3) to study the recommendations for the development of roles for promoting Buddhist Affairs based on 4 Virtues for a Good Household Life of Roi Et office of Buddhism. It was a Descriptive Study. The population used in this research were 6,372 clergy in the administrative area of Roi Et province. Assigned the sample, using the Krejcie & Morgan formula, 364 samples were obtained. There were 364 samples. The instrument used for data collection was a questionnaire with a                     5-level estimation scale. The statistics used to analyze the data were percentage, mean, standard deviation, and One-way ANOVA analysis of variance (F-test).            The results showed that: 1. The role of promoting Buddhist affairs based on 4 Virtues for a Good Household Life of Roi Et office of Buddhism, overall and side was at a high level. When considering each aspect, sorted from the highest aspect to the lowest averages, namely: Social welfare education (Tama), followed by Administration (Khanti), and the side with the lowest mean was religious studies (Tama). 2. The results of the comparison of the level of opinions on the roles for promoting Buddhist Affairs based on 4 Virtues for a Good Household Life of Roi Et office of Buddhism, classified by age, years of ordination, education level. Overall, level of education, administrative (Khanti) and welfare education, (Tama), the clergy with an education level below bachelor’s degree and Bachelor’s and the Master degree had different opinions at the .05 level of significance 3. Suggestions on the roes in promoting in Buddhist affairs based on 4 Virtues for a Good Household Life of Roi Et office of Buddhism found that there should be an inspection and evaluation of the performance regularly for as to know about the problems or bugs in order to improve and develop more next time, teaching and dissemination of doctrines with modern methods through online media, Religious education promotion, Pali department, or Dharma should be organized, throughout helping to support various educational institutions to be more coordinating with relevant agencies, helping the poor and suffering, there should be activities to maintain cleanliness within the temple, manage the budget to support the establishment of an  education and fun at the primary, secondary, and higher education levels for the benefit of students who were good people and study well but were disadvantaged in  education.